2008
DOI: 10.1080/02713680701861752
|View full text |Cite
|
Sign up to set email alerts
|

Serum Alpha-1-Antitriypsin Levels in Patients with Pseudoexfolative Syndrome

Abstract: Serum AAT levels were found to be increased in patients with PEX. Increased serum AAT levels in PEX may explain the role of inflammation in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 13 By contrast, Sorkhabi et al has reported increased level of serum TNF-α to be risk a factor for systemic and ocular manifestations in patients with XFS (without glaucoma). 19 Similarly, there have been investigations where systemic inflammatory markers such as serum alpha 1-antitrypsin activity, 20 YKL-40, 21 high-sensitivity C-reactive protein 19 and neutrophil-to-lymphocyte ratio 22 have been associated with XFS/PEG.…”
Section: Discussionmentioning
confidence: 99%
“… 13 By contrast, Sorkhabi et al has reported increased level of serum TNF-α to be risk a factor for systemic and ocular manifestations in patients with XFS (without glaucoma). 19 Similarly, there have been investigations where systemic inflammatory markers such as serum alpha 1-antitrypsin activity, 20 YKL-40, 21 high-sensitivity C-reactive protein 19 and neutrophil-to-lymphocyte ratio 22 have been associated with XFS/PEG.…”
Section: Discussionmentioning
confidence: 99%
“…21 Elevated levels of homocysteine in PEX patients with and without glaucoma may partly explain the increased risk of vascular disease among patients with PEX. 13,17,18 Cumurcu et al 22 reported that serum a-1 antitrypsin, an acute phase protein associated with inflammatory processes, is increased in patients with PEX. However, the results of our study showed no statistically significant difference in hsCRP levels between the XFS, XFG, and control participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Turkyilmaz et al 24 have shown a relationship between PES and elevated serum levels of YKL-40 (chitinase-3-like protein 1), which has a role in endothelial dysfunction and inflammation. To date, elevated serum levels of several other molecules that have definitive roles in inflammatory processes (eg, cardiovascular and cerebrovascular disease, endothelial dysfunction), including high-sensitivity C-reactive protein, 25 tumor necrosis factora, 25 antiphospholipid antibody, 26 a 1-antitrypsin, 27 homocysteine, 28 and hydroxyproline 29 have been studied in the serum of patients with PES. In the present study, serum omentin levels were found to be lower in patients with PES compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%